Use of antiseptic mouthrinse during pregnancy and pregnancy outcomes: a randomised controlled clinical trial in rural China. (14th September 2016) - Jiang, H; Xiong, X; Su, Y; Peng, J; Zhu, X; Wang, J; Chen, M; Qian, X
Abstract : Objective: To determine whether an antimicrobial mouthrinse intervention reduces adverse pregnancy outcomes in a low‐resource rural area. Design: Randomised controlled trial. Setting: A county‐level maternal health care hospital in China. Sample: Pregnant women of less than 20 weeks of gestation having periodontal disease. Methods: Women with periodontal disease were randomised into the intervention ( n = 232) and control group ( n = 234). Participants in the intervention group were provided with free mouthrinse (alcohol‐free mouthrinse containing 0.7% cetylpyridinium chloride) throughout the pregnancy and given education on oral health. Women in the control group only received oral hygiene education. All participants had a periodontal re‐examination at the third trimester and were followed‐up to childbirth. Main outcome measures: The primary outcome was gestational age. Secondary outcomes included birthweight, periodontal disease score, pregnancy complications (small‐for‐gestational‐age, gestational hypertension, gestational diabetic mellitus, severe anaemia, premature rupture of membrane). Results: The general periodontal status of the intervention group at the third trimester was significantly better than that of the control group (measured by periodontal disease score: 11.26 ± 3.60 versus 11.92 ± 3.01; P = 0.04). There was no difference in pregnancy outcome between the two groups except for premature rupture of the membranes. The women in the intervention group had a significantly reduced risk of premature rupture of the membranes compared with the control group (1.4 versus 5.7%, OR = 0.23, 95% CI 0.07–0.84; P = 0.03). Conclusions: The mouthrinse intervention during pregnancy improved periodontal health. The intervention did not lead to a change in gestational age but it reduced the rate of premature membrane rupture. Further studies are needed to explore the biological mechanism of this association. Tweetable abstract: Use of antiseptic mouthrinse during pregnancy may improve maternal oral health and pregnancy outcomes. Tweetable abstract: Use of antiseptic mouthrinse during pregnancy may improve maternal oral health and pregnancy outcomes.